A method for preparing block aerogel using coal gangue

Boehmite fiber sol and silica sol were prepared by calcining activated coal gangue, combined with hydrophobic modification treatment, and the problem of underutilization and complex decomposition process in the prior art was solved, and a high mechanical properties and extensive preparation was prepared A block aerogel for application prospects.

CN116283209BActive Publication Date: 2024-12-24CHINA UNIV OF MINING & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310040217.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-12
Publication Date
2024-12-24
Estimated Expiration
2043-01-12

AI Technical Summary

Technical Problem

The existing methods of making aerogels using coal gangue have problems such as underutilization of aluminum elements, complex decomposition removal process, high cost, and poor mechanical properties of the finished product.

Method used

By calcining activated coal gangue powder, boehmite fiber sol and silica sol were prepared, combined with hydrophobic modification treatment, and mass aerogels were prepared by normal pressure drying, adjusting pH value for impurities, improving the utilization efficiency of aluminum elements and gas Mechanical properties of gel.

Benefits of technology

It realizes more efficient use of aluminum elements in coal gangue, reduces the cost of removal, improves the structural integrity and porosity of the aerogel, enhances its mechanical properties, and expands its application prospects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A method for preparing block aerogel using coal gangue, comprising the following steps: first, coal gangue is crushed and calcined for activation, and filtered after acid leaching to obtain an aluminum-rich solution and an acid leaching residue; ammonia water is dripped into the aluminum-rich solution to adjust the pH to 3-4, filtered after standing, and ammonia water is continuously dripped into the filtrate to adjust the pH to 4-6 to obtain an aluminum hydroxide suspension, the suspension is generated under hydrothermal conditions, and the boehmite fiber is cleaned to prepare a sol for standby use; the acid leaching residue is dissolved in a NaOH solution, and hydrochloric acid is dripped to adjust the pH to 2-4 to prepare a silica sol; the boehmite fiber sol and the silica sol are mixed and stirred evenly, ammonia water is dripped to obtain a wet gel, and then the wet gel is subjected to hydrophobic modification, solvent replacement, and dried to obtain a block aerogel. The method is simple in process, low in cost, can make full use of the silicon and aluminum elements in coal gangue, and the prepared block aerogel has a complete structure, high porosity, good mechanical properties, and a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aerogel preparation, and in particular to a method for preparing block aerogel by utilizing coal gangue. Background Art

[0002] Gangue is a type of solid waste from mining, which is solid waste discharged during excavation, mining and coal washing. The escape or leaching of sulfides in gangue will pollute the atmosphere, farmland and water bodies. Gangue mountains can also spontaneously combust and cause fires, or collapse during the rainy season, silting up rivers and causing disasters, which has a huge impact on environmental governance. At present, gangue is mainly used for road paving, backfilling, thermal power generation and building materials. The added value of recycling is low, and the silicon and aluminum elements rich in gangue are not well utilized.

[0003] Aerogel is a new type of amorphous porous material with nano-scale pore structure and air as the filling medium. It has many unique physical and chemical properties such as low density, low thermal conductivity, high porosity, and high specific surface area. As a representative of new amorphous lightweight porous materials, aerogel has good thermal insulation properties. However, due to the expensive raw materials and strict process conditions, it is difficult to achieve large-scale industrial production of aerogel, which greatly limits the application of aerogel materials. Therefore, using the silicon and aluminum elements in coal gangue to make aerogel can not only turn waste into treasure, but also has great added value.

[0004] The current method of making aerogel from coal gangue is to extract the silicon and aluminum elements in the coal gangue to make silica aerogel or silica / alumina aerogel. The current method of making aerogel from coal gangue has the following main disadvantages: (1) The silica aerogel made from coal gangue does not fully utilize the aluminum element in the coal gangue, resulting in a waste of aluminum element; (2) In the traditional process of making silica / alumina aerogel, the silica and aluminum element extract of coal gangue contains impurity ions, which are often removed by multiple solvent replacements or ionic liquids. The impurity removal process is complicated and costly; (3) The mechanical properties of the aerogel currently made from coal gangue are poor, and the finished product is mostly powder, which greatly limits the scope of use of the finished product. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing block aerogel using coal gangue. The method has simple process, low cost, can make full use of silicon and aluminum elements in the coal gangue, and the prepared block aerogel has a complete structure, high porosity, good mechanical properties and broader application prospects.

[0006] To achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing block aerogel using coal gangue comprises the following steps:

[0007] S1, crushing and grinding the coal gangue and calcining it to obtain activated coal gangue powder;

[0008] S2, soaking the activated gangue powder in deionized water for 10 to 20 minutes, then filtering and washing with deionized water, and soaking the obtained water-leached residue in acid at a temperature of 90 to 100° C. for 3.5 to 4 hours to obtain an acid-leached residue and an aluminum-rich solution;

[0009] S3, preparation of boehmite fiber sol and silica sol;

[0010] The preparation process of the boehmite fiber sol is as follows:

[0011] S3-1, adding aqueous ammonia to the aluminum-rich solution obtained in step S2, adjusting the pH of the aluminum-rich solution to 3.5, letting it stand for 1 to 2 hours and then filtering, and continuing to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0012] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing a hydrothermal reaction at a temperature of 180 to 220° C. for 24 to 26 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0013] S3-3, mixing water and anhydrous ethanol in a mass ratio of (1-1.2):1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 30-40 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;

[0014] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved in a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 2-4, and the silica sol is obtained after fully stirring;

[0015] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1: (4-6) and stirring them uniformly to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 5-8, and leaving it to stand for 24-36 hours to obtain a wet gel;

[0016] S5, modifying the wet gel obtained in step S4 by soaking it in a hydrophobic modifier at a temperature of 20 to 30° C. for 24 to 30 hours to obtain a modified wet gel;

[0017] S6. The modified wet gel obtained in step S5 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C. to obtain a block aerogel.

[0018] Preferably, in step S1, the coal gangue is crushed and ground to 150-250 mesh, and calcined at 750-1100° C. for 1-3 hours.

[0019] Preferably, in step S2, the acid is prepared by mixing hydrochloric acid and acetic acid in a molar ratio of (7-8):1, and the concentration of hydrochloric acid in the acid is 8 mol / L.

[0020] Preferably, in step S5, the hydrophobic modifier is trimethylchlorosilane.

[0021] Preferably, in step S6, each drying time is 24 hours.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) The present invention utilizes coal gangue waste, manufactures aluminum in the coal gangue into boehmite fibers, and then implants aerogels. The obtained aerogels have better mechanical properties, improve the utilization efficiency of aluminum, and the obtained finished products have broader application prospects.

[0024] (2) The present invention extracts silicon and aluminum elements separately and removes impurities by adjusting the pH, and the impurity removal process is simple and low-cost;

[0025] (3) The present invention prepares a sol of boehmite fiber and mixes it with a silica sol before gelling, so that the boehmite fiber can be distributed more evenly and combined more tightly with the aerogel; at the same time, by adjusting the ratio of the boehmite fiber sol and the silica sol, the aerogel can have a better skeleton structure and better controllability.

[0026] (4) The present invention obtains a stronger skeleton structure through boehmite fiber, and reduces the capillary force generated during the drying process through hydrophobic modification. It can produce block aerogel with complete structure, high porosity and good mechanical properties under normal pressure environment, thereby reducing production costs. The obtained finished product can be used as a thermal insulation material or adsorption material, and has a broader application prospect. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments.

[0028] Embodiment 1

[0029] A method for preparing block aerogel using coal gangue comprises the following steps:

[0030] S1, crushing and grinding the coal gangue to 250 mesh, and calcining at 1100°C for 1h to obtain activated coal gangue powder;

[0031] S2, soaking the activated gangue powder in deionized water for 10 minutes, then filtering and washing with deionized water, soaking the obtained water-leached residue in acid at a temperature of 90° C. for 4 hours to obtain acid-leached residue and aluminum-rich solution, wherein the acid is a mixture of hydrochloric acid and acetic acid in a molar ratio of 7:1, and the concentration of hydrochloric acid in the acid is 8 mol / L;

[0032] S3, preparation of boehmite fiber sol and silica sol;

[0033] The preparation process of the boehmite fiber sol is as follows:

[0034] S3-1, add aqueous ammonia to the aluminum-rich solution obtained in step S2, adjust the pH of the aluminum-rich solution to 3.5, let it stand for 1 hour and then filter, continue to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0035] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing hydrothermal reaction at 180° C. for 26 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0036] S3-3, mixing water and anhydrous ethanol in a mass ratio of 1:1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 30 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;

[0037] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved with a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 3, and the silica sol is obtained after fully stirring;

[0038] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1:6 and stirring to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 5, and leaving it to stand for 24 hours to obtain a wet gel;

[0039] S5, modifying the wet gel obtained in step S4 by soaking in trimethylchlorosilane, a hydrophobic modifier, at 20° C. for 24 hours to obtain a modified wet gel;

[0040] S6. The modified wet gel obtained in step S5 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C., respectively. The drying time for both drying times is 24 h, and finally an aerogel is obtained.

[0041] The aerogel prepared in this example has a compressive strength of 2.89 MPa and a thermal conductivity of 0.0152 W·m -1 ·k -1, density is 0.124 g·cm -1 , the porosity reaches 91.3%.

[0042] Embodiment 2

[0043] A method for preparing block aerogel using coal gangue comprises the following steps:

[0044] S1, crushing and grinding the coal gangue into 150 mesh, and calcining at 750°C for 3h to obtain activated coal gangue powder;

[0045] S2, soaking the activated gangue powder in deionized water for 20 minutes, then filtering and washing with deionized water, soaking the obtained water-leached residue in acid at a temperature of 90° C. for 3.5 hours to obtain an acid-leached residue and an aluminum-rich solution, wherein the acid is a mixture of hydrochloric acid and acetic acid in a molar ratio of 8:1, and the concentration of hydrochloric acid in the acid is 8 mol / L;

[0046] S3, preparation of boehmite fiber sol and silica sol;

[0047] The preparation process of the boehmite fiber sol is as follows:

[0048] S3-1, add aqueous ammonia to the aluminum-rich solution obtained in step S2, adjust the pH of the aluminum-rich solution to 3.5, let it stand for 2 hours and then filter, continue to add aqueous ammonia to the filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0049] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing hydrothermal reaction at 220° C. for 24 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0050] S3-3, mixing water and anhydrous ethanol in a mass ratio of 1:1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 40 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;

[0051] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved with a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 4, and the silica sol is obtained after fully stirring;

[0052] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1:6 and stirring to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 8, and leaving it to stand for 36 hours to obtain a wet gel;

[0053] S5, modifying the wet gel obtained in step S4 by soaking in trimethylchlorosilane, a hydrophobic modifier, at 30° C. for 30 h to obtain a modified wet gel;

[0054] S6. The modified wet gel obtained in step S5 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C., respectively. The drying time for both drying times is 24 h, and finally an aerogel is obtained.

[0055] The aerogel prepared in this example has a compression strength of 3.01 MPa and a thermal conductivity of 0.0157 W·m -1 ·k -1 , density is 0.132 g·cm -1 , the porosity reaches 90.1%.

[0056] Embodiment 3

[0057] A method for preparing block aerogel using coal gangue comprises the following steps:

[0058] S1, crushing and grinding the coal gangue to 250 mesh, and calcining at a high temperature of 1100°C for 3h to obtain activated coal gangue powder;

[0059] S2, soaking the activated gangue powder in deionized water for 20 minutes, then filtering and washing with deionized water, soaking the obtained water-leached residue in acid at a temperature of 100° C. for 4 hours to obtain acid-leached residue and aluminum-rich solution, wherein the acid is a mixture of hydrochloric acid and acetic acid in a molar ratio of 7:1, and the concentration of hydrochloric acid in the acid is 8 mol / L;

[0060] S3, preparation of boehmite fiber sol and preparation of silica sol;

[0061] The preparation process of the boehmite fiber sol is as follows:

[0062] S3-1, adding aqueous ammonia to the aluminum-rich solution obtained in step S2, adjusting the pH of the aluminum-rich solution to 3.5, letting it stand for 2 hours and then filtering, and continuing to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0063] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing hydrothermal reaction at 200° C. for 24 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0064] S3-3, mixing water and anhydrous ethanol in a mass ratio of 1.2:1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 40 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;

[0065] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved with a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 2, and the silica sol is obtained after fully stirring;

[0066] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1:6 and stirring to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 6, and leaving it to stand for 24 hours to obtain a wet gel;

[0067] S5, modifying the wet gel obtained in step S4 by soaking it in trimethylchlorosilane, a hydrophobic modifier, at 25° C. for 30 hours to obtain a modified wet gel;

[0068] S6. The modified wet gel obtained in step S6 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C., respectively. The drying time for both drying times is 24 h, and finally an aerogel is obtained.

[0069] The aerogel prepared in this example has a compressive strength of 2.62 MPa and a thermal conductivity of 0.0145 W·m -1 ·k -1 , density is 0.115 g·cm -1 , the porosity reaches 92.1%.

[0070] Embodiment 4

[0071] A method for preparing block aerogel using coal gangue comprises the following steps:

[0072] S1, crushing and grinding the coal gangue to 250 mesh, and calcining at a high temperature of 1100°C for 1h to obtain activated coal gangue powder;

[0073] S2, soaking the activated gangue powder in deionized water for 10 minutes, then filtering and washing with deionized water, soaking the obtained water-leached residue in acid at a temperature of 90° C. for 4 hours to obtain acid-leached residue and aluminum-rich solution, wherein the acid is a mixture of hydrochloric acid and acetic acid in a molar ratio of 7:1, and the concentration of hydrochloric acid in the acid is 8 mol / L;

[0074] S3, preparation of boehmite fiber sol and preparation of silica sol;

[0075] The preparation process of the boehmite fiber sol is as follows:

[0076] S3-1, adding aqueous ammonia to the aluminum-rich solution obtained in step S2, adjusting the pH of the aluminum-rich solution to 3.5, letting it stand for 2 hours and then filtering, and continuing to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0077] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing hydrothermal reaction at 180° C. for 24 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0078] S3-3, mixing water and anhydrous ethanol in a mass ratio of 1:1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 40 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;

[0079] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved with a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 3, and the silica sol is obtained after fully stirring;

[0080] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1:4 and stirring to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 5, and leaving it to stand for 24 hours to obtain a wet gel;

[0081] S5, modifying the wet gel obtained in step S4 by soaking in trimethylchlorosilane, a hydrophobic modifier, at 20° C. for 24 hours to obtain a modified wet gel;

[0082] S6. The modified wet gel obtained in step S6 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C., respectively. The drying time for both drying times is 24 h, and finally an aerogel is obtained.

[0083] The aerogel prepared in this example has a compression strength of 5.18 MPa and a thermal conductivity of 0.0166 W·m -1 ·k -1 , density is 0.185 g·cm -1 , the porosity reaches 88.4%.

[0084] Embodiment 5

[0085] A method for preparing block aerogel using coal gangue comprises the following steps:

[0086] S1, crushing and grinding the coal gangue into 150 mesh, and calcining at 750°C for 3h to obtain activated coal gangue powder;

[0087] S2, soaking the activated gangue powder in deionized water for 20 minutes, then filtering and washing with deionized water, soaking the obtained water-leached residue in acid at a temperature of 90° C. for 3.5 hours to obtain acid-leached residue and aluminum-rich solution, wherein the acid is a mixture of hydrochloric acid and acetic acid in a molar ratio of 8:1, and the concentration of hydrochloric acid in the acid is 8 mol / L;

[0088] S3, preparation of boehmite fiber sol and preparation of silica sol;

[0089] The preparation process of the boehmite fiber sol is as follows:

[0090] S3-1, adding aqueous ammonia to the aluminum-rich solution obtained in step S2, adjusting the pH of the aluminum-rich solution to 3.5, letting it stand for 1 hour and then filtering, and continuing to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0091] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing a hydrothermal reaction at 220° C. for 26 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0092] S3-3, mixing water and anhydrous ethanol in a mass ratio of 1:1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 30 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;.

[0093] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved with a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 4, and the silica sol is obtained after fully stirring.

[0094] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1:4 and stirring to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 8, and leaving it to stand for 36 hours to obtain a wet gel;

[0095] S5, modifying the wet gel obtained in step S4 by soaking in trimethylchlorosilane, a hydrophobic modifier, at 30° C. for 30 h to obtain a modified wet gel;

[0096] S6. The modified wet gel obtained in step S6 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C., respectively. The drying time for both drying times is 24 h, and finally an aerogel is obtained.

[0097] The aerogel prepared in this example has a compression strength of 5.27 MPa and a thermal conductivity of 0.0170 W·m -1 ·k-1 , density is 0.196 g·cm -1 , the porosity reaches 87.9%.

[0098] Embodiment 6

[0099] A method for preparing block aerogel using coal gangue comprises the following steps:

[0100] S1, crushing and grinding the coal gangue to 250 mesh, and calcining at a high temperature of 1100°C for 3h to obtain activated coal gangue powder;

[0101] S2, soaking the activated gangue powder in deionized water for 20 minutes, then filtering and washing with deionized water, soaking the obtained water-leached residue in acid at a temperature of 100° C. for 4 hours to obtain acid-leached residue and aluminum-rich solution, wherein the acid is a mixture of hydrochloric acid and acetic acid in a molar ratio of 7:1, and the concentration of hydrochloric acid in the acid is 8 mol / L;

[0102] S3, preparation of boehmite fiber sol and preparation of silica sol;

[0103] The preparation process of the boehmite fiber sol is as follows:

[0104] S3-1, adding aqueous ammonia to the aluminum-rich solution obtained in step S2, adjusting the pH of the aluminum-rich solution to 3.5, letting it stand for 2 hours and then filtering, and continuing to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5 to obtain an aluminum hydroxide suspension;

[0105] S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing hydrothermal reaction at 200° C. for 24 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber;

[0106] S3-3, mixing water and anhydrous ethanol in a mass ratio of 1.2:1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 40 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5;

[0107] The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved with a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 2, and the silica sol is obtained after fully stirring;

[0108] S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1:4 and stirring to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 6, and leaving it to stand for 24 hours to obtain a wet gel;

[0109] S5, modifying the wet gel obtained in step S4 by soaking it in trimethylchlorosilane, a hydrophobic modifier, at 25° C. for 30 hours to obtain a modified wet gel;

[0110] S6. The modified wet gel obtained in step S6 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C., respectively. The drying time for both drying times is 24 h, and finally an aerogel is obtained.

[0111] The aerogel prepared in this example has a compressive strength of 5.10 MPa and a thermal conductivity of 0.0161 W·m -1 ·k -1 , density is 0.178 g·cm -1 , the porosity reaches 89.2%.

Claims

1. A method for preparing block aerogel using coal gangue, characterized in that: The following steps are involved: S1, crushing and grinding the coal gangue and calcining it to obtain activated coal gangue powder; S2, soaking the activated gangue powder in deionized water for 10 to 20 minutes, then filtering and washing with deionized water, and soaking the obtained water-leached residue in acid at a temperature of 90 to 100° C. for 3.5 to 4 hours to obtain an acid-leached residue and an aluminum-rich solution; S3, preparation of boehmite fiber sol and silica sol; The preparation process of the boehmite fiber sol is as follows: S3-1, adding aqueous ammonia to the aluminum-rich solution obtained in step S2, adjusting the pH of the aluminum-rich solution to 3.5, letting it stand for 1 to 2 hours and then filtering, and continuing to add aqueous ammonia to the obtained filtrate to adjust the pH of the filtrate to 5, to obtain an aluminum hydroxide suspension; S3-2, pouring the aluminum hydroxide suspension obtained in step S3-1 into a hydrothermal kettle, placing the hydrothermal kettle in a constant temperature oven, performing a hydrothermal reaction at a temperature of 180 to 220° C. for 24 to 26 hours, cooling and centrifuging to obtain a product, and washing the product with deionized water several times to obtain boehmite fiber; S3-3, mixing water and anhydrous ethanol in a mass ratio of (1-1.2):1 to obtain a mixed solution, adding the boehmite fiber obtained in step S3-2, and stirring in a water bath for 30-40 minutes to obtain a boehmite fiber sol, wherein the mass ratio of the boehmite fiber to the mixed solution is 1:15.5; The preparation process of the silica sol is as follows: the acid leaching residue obtained in step S2 is fully dissolved in a sodium hydroxide solution, and then hydrochloric acid is added dropwise to adjust the pH of the silica sol to 2-4, and the silica sol is obtained after fully stirring; S4, mixing the boehmite fiber sol and the silica sol obtained in step S3 in a volume ratio of 1: (4-6) and stirring them uniformly to obtain a mixed sol, then dropping ammonia water into the mixed sol to adjust the pH to 5-8, and leaving it to stand for 24-36 hours to obtain a wet gel; S5, modifying the wet gel obtained in step S4 by soaking it in a hydrophobic modifier at a temperature of 20 to 30° C. for 24 to 30 hours to obtain a modified wet gel; S6. The modified wet gel obtained in step S5 is subjected to solvent replacement with n-hexane, and finally subjected to graded drying at normal pressure at temperatures of 60° C. and 70° C. to obtain a block aerogel.

2. The method for preparing block aerogel using coal gangue according to claim 1, characterized in that: In step S1, the coal gangue is crushed and ground to 150-250 meshes, and calcined at 750-1100° C. for 1-3 hours.

3. A method for preparing block aerogel using coal gangue according to claim 1 or 2, characterized in that: In step S2, the acid is prepared by mixing hydrochloric acid and acetic acid in a molar ratio of (7-8):1, and the concentration of hydrochloric acid in the acid is 8 mol / L.

4. A method for preparing block aerogel using coal gangue according to claim 1 or 2, characterized in that: In step S5, the hydrophobic modifier is trimethylchlorosilane.

5. The method for preparing block aerogel using coal gangue according to claim 1 or 2, characterized in that: In step S6, each drying time is 24 hours.